دور المعايير الدولية للمحاسبة والإبلاغ المالي في تفعيل حوكمة الشركات - زغوان سفيان (University Of Eloued جامعة الوادي, 2023)
تهدف هذه الدراسة للتعرف على دور المعايير الدولية للمحاسبة والإبلاغ المالي في تفعيل حوكمة الشركات، ولتحقيق أهداف الدراسة تم الإعتماد على إختيار المنهج الوصفي التحليلي بإعتباره منهجا مناسبا، وأستخدمت الإستبانة كأداة لجمع البيانات من عينة الدراسة والمتمثلة في مجموعة من المهنيين والأكاديميين والمهتمين بمجال المحاسبة داخل الجزائر. وخلصت الدراسة إلى العديد من النتائج أهمها أن تطبيق المعايير الدولية للمحاسبة والإبلاغ المالي يعزز من عملية الإفصاح والشفافية ويؤدي إلى تحسين جودة المعلومة المحاسبية وهو ما ينعكس إيجابا على تطبيق وتفعيل حوكمة الشركات، كما خلصت أيضا إلى أن الجزائر تحتاج للعديد من الخطوات الجدية حتى تصل إلى التطبيق الفعلي والجيد لحوكمة الشركات. وإستنادا إلى نتائج الدراسة قدمت مجموعة من التوصيات أهمها ضرورة تحيين النظام المحاسبي المالي الجزائري لمواكبة تغيرات المعايير الدولية للمحاسبة والإبلاغ المالي، إضافة إلى ضرورة الإسراع بإنشاء معهد وطني لحوكمة الشركات يسهر على تطبيق ميثاق الحكم الراشد وتفعيل حوكمة الشركات. This study aims to identify the role of adopting international accounting and Financial Reporting Standards in activating corporate governance, and to achieve the objectives of the study, the descriptive curriculum test was adopted as an appropriate approach, and the questionnaire was used as a tool to collect data from the study sample represented by a group of professionals, academics, and those interested in the field of accounting within Algeria The study concluded many results, the most important of which is that the application of international accounting and Financial Reporting Standards enhances the disclosure and transparency process and leads to improving the quality of accounting information, which is reflected positively on the application and activation of corporate governance, and also concluded that Algeria needs many serious steps to reach the actual and good application of corporate governance. Based on the results of the study, a set of recommendations were presented, the most important of which is the need to update the Algerian financial accounting system to keep pace with changes in international standards for accounting and financial reporting, in addition to the need to expedite the establishment of a national institute for corporate governance that oversees the implementation of the Charter of Good Governance and the activation of corporate governance.
دراسة ميدانية
أطروحة
Keywords: معايير المحاسبة والإبلاغ المالي الدولية; حوكمة الشركات; جودة المعلومة المحاسبية; الإفصاح والشفافية; International Accounting and Financial Reporting Standards; corporate governance; accounting information quality; disclosure and transparency.